Effect of corrective exercises on functional spinal deformities in preschool and school-aged children - Biševac, Emir; Mahmutović, Elvis; Mekić, Raid; Dolićanin, Zana (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Poor muscle development, accompanied by insufficient physical activity and non-physiological forces which act on the bone and joint system, often causes improper body posture. Objectives. To examine whether performing corrective exercises which stretch shortened and strengthen weakened muscles regularly can improve body posture in preschool and school-aged children. Methods. The prospective study included 110 children, 63 (57.2%) boys and 47 (42.8%) girls (the average age being 6.6 ± 2.4). Corrective exercises were performed four times a week for six months, in periods of 90 minutes. We used somatoscopy and somatometry methods to assess body posture. Results. On the initial checkup it was found that 18 children (16.4%) had some kind of spine deformity; 11 of them (10%) had scoliosis, six (5.5%) had kyphosis and 1(0.9%) had lordotic body posture. The first follow-up checkup was performed 3 months later when we found a decrease in the number of children with a bad body posture. The second follow-up checkup was repeated 6 months later. Out of 18 children (16.4%) who had been registered at the beginning, 4 (3.6%) had scoliotic, 2 (1.8%) had kyphotic and 1 (0.9%) had lordotic posture 6 months later. Conclusion. Based on the obtained results, it can be said that regular performance of corrective exercises (strengthening weakened and stretching shortened muscles) for six months had a positive effect on certain spine deformities. Kyphosis correction was visible after only three months, scoliosis correction was visible after six months, while lordosis correction was not achieved by corrective exercises in the only registered case.